(untitled) (CIPEEX, 2024)
WOMEN ARE INCREASINGLY GAINING SPACE IN THE ECONOMIC, SOCIAL, AND POLITICAL ARENAS. MORE AND MORE WOMEN ARE PARTICIPATING IN BUSINESS, OPENING COMPANIES, EMBARKING ON ENTREPRENEURIAL VENTURES, AND BECOMING LEADERS IN THEIR FIELDS OF ACTIVITY. A METHODOLOGY USED IS DESCRIPTIVE RESEARCH OF A QUALITATIVE NATURE, AND THE DATA COLLECTION INSTRUMENTS USED WAS THE QUESTIONNAIRE MADE AVAILABLE THROUGH A LINK IN THE MEDIA DEVELOPED BY THE AUTHOR AND ANALYZED THROUGH GOOGLE FORMS. IN THIS WAY, MANY WOMEN TEND TO EMBARK ON ENTREPRENEURIAL VENTURES TO IMPROVE THEIR FINANCIAL SITUATION AND PURSUE OPPORTUNITIES, BUT EACH ONE HAS DIFFERENT ENTREPRENEURIAL CHARACTERISTICS. FROM THIS PERSPECTIVE, THE MAIN OBJECTIVE OF THIS RESEARCH WAS TO DESCRIBE THE FEMALE ENTREPRENEURIAL PROFILE IN THE CITY OF CRIXÁS-GO, HIGHLIGHTING THE CHARACTERISTICS OF WOMEN ENTREPRENEURS AND THEIR INITIATIVES TO ESTABLISH NEW BUSINESSES AND HOW THEY HAVE ENTERED THE ENTREPRENEURSHIP, AND DETERMINE THE ENTREPRENEURIAL PROFILE. AIMING TO ANSWER THE FOLLOWING QUESTIONS: WHAT ARE THE ENTREPRENEURIAL PROFILES AND FIELD OF ACTIVITY OF THE WOMEN INCLUDED IN THE JOB MARKET OF CRIXÁS-GO? WHEN CALCULATING THE RESULTS, ENTREPRENEURIAL CHARACTERISTICS WERE IDENTIFIED IN THE INTERVIEWEES SUCH AS MOTIVATION, PERSISTENCE, DESIRE TO SUCCEED, AND THE VAST MAJORITY OF WOMEN PRESENTED THE PROFILE OF AN ENTREPRENEUR OUT OF NECESSITY, DESPITE FACING DIFFICULTIES IN TAKING CALCULATED RISKS AND JUGGLING MULTIPLE TASKS SUCH AS BEING A MOTHER, WIFE, AND HOUSEWIFE. FURTHERMORE, THE MAJORITY OF FEMALE ENTREPRENEURS PRESENTED A HIGHER EDUCATION LEVEL, AND ONE OF THEIR BIGGEST CHALLENGES WAS HAVING SYSTEMATIC PLANNING AND MONITORING.